Public School Food Supply Chain during the COVID-19 Pandemic: A Case Study of the City of Vitoria (Brazil) - Coelho, Taniellen Miranda; Moscon, Julianna Zambon; Brito Junior, Irineu de [UNESP]; Mendes, Angelica Alebrant; Yoshida Yoshizaki, Hugo Tsugunobu (Mdpi, 2022)
Background: Due to the COVID-19 pandemic, Brazilian public schools closed in 2020. This lockdown stopped the provision of school meals to public school students, most of whom belonged to low-income families facing food insecurity. To guarantee the students' food security during this period, food items previously provided through school meals were converted into food kits and delivered to the students' families. Methods: This case study analyzes the logistical impacts of this change in the school food supply chain concerning the legislation, procurement, assembly, and distribution of food kits in the city of Vitoria, Brazil. We interviewed suppliers and workers of the Municipal Secretariat of Education and distributed a survey to professionals and beneficiaries. Results: One of the findings was that federal procurement regulations for the acquisition of food for public schools led to difficult choices for school officials during this period. These regulations determined that at least 30% of the budget must be used in local purchases from smallholder family farmers. However, almost all products generated by family farming in the region of Vitoria are perishable and require distribution and consumption on the same day, which represents a challenge for the logistic process of assembling and distributing food kits. The solution was the selection of eggs as the primary protein item in the kits. Conclusions: The lessons learned through this study suggest potential actions that would make this supply chain more resilient in future emergencies.
Keywords: school feeding; food security; COVID-19 pandemic; distribution; supply chain management; legislation